Pengurusan penilaian prestasi guru di sekolah kebangsaan daerah Kota Tinggi - Unos, Noryati (2013)
This study was conducted to see the appraisal management among teachers in Felda Lok Heng cluster schools in Kota Tinggi District, Johor. This quantitative study aimed to identify the level of management and performance evaluation of teachers' perceptions of performance appraisal practices exercised by administrator. To identify whether demographic factors such as gender, age and length of service affect the level of knowledge and perception of teachers . A total of 60 teachers from three schools in Felda Lok Heng cluster consisting of two primary schools and a secondary school selected. All data were analyzed using Statistical Package for Social Sciences (SPSS) version 16.00. To achieve this purpose, a survey conducted has used questionnaire survey as a instrument for quantitative studies. These data were generated using descriptive and inferential statistics. Findings showed that the performance appraisal management at a high level mean of 3.95. In the aspect of teachers' perception of administrator performance evaluation management practices are also at a high level with a mean of 3.64. Suggestion is given as an improvement proposal that the level of knowledge and performance evaluation of management practices remain outstanding. The findings of the T-test showed no significant difference on the level of knowledge and perception of gender. ANOVA findings also, showed no significant difference on the level of knowledge and perception of teachers in practice according to age and length of service